(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
In this article, the issues of anthropocentric analysis of idioms are studied based on linguistic and cognitive approaches. The study analyzes the dependence of language on the human factor, that is, how the worldview, national thinking, cultural values, and psychological states of the people are reflected in idioms. Within the anthropocentric paradigm, idioms are considered as linguistic units inextricably linked with human experience, emotions, and social relations. The article highlights the semantic structure of idioms, their pragmatic functions in the speech process, and their communicative significance. The research results allow us to interpret idiomatic units as a product of human thought and demonstrate the relevance of the anthropocentric approach in modern linguistics.